Luxury Fashion - Bilro, R.G.; Custódio, C.M.; Marques, S. (International Encyclopedia of Business Management, 2026)
Luxury, a concept steeped in history, remains multifaceted and constantly evolving. Traditionally linked to exclusivity and elite privilege, it has transitioned in the modern era into a dynamic sector accessible to a broader audience. This shift is fueled by emerging affluent consumers, increased purchasing power, and reduced production costs, alongside innovative business models and digital transformation. Defined by exceptional quality, exclusivity, and symbolic value, luxury transcends material possessions, incorporating experiences and emotions that resonate deeply with consumers. The luxury fashion industry represents the largest share of the global personal luxury goods market. Luxury fashion blends exceptional craftsmanship, innovative design, and cultural heritage with modernity and trendiness, offering products that are not only desirable but also lined with prestige and societal coherence. It bridges art and utility, providing both elite aspirations and broader consumer demographics. Luxury brands maintain their distinctiveness through meticulous attention to quality, storytelling, and customer experience while adapting to new market demands and preserving their heritage.